2018
DOI: 10.1016/j.celrep.2018.11.098
|View full text |Cite
|
Sign up to set email alerts
|

Culling Less Fit Neurons Protects against Amyloid-β-Induced Brain Damage and Cognitive and Motor Decline

Abstract: SummaryAlzheimer’s disease (AD) is the most common form of dementia, impairing cognitive and motor functions. One of the pathological hallmarks of AD is neuronal loss, which is not reflected in mouse models of AD. Therefore, the role of neuronal death is still uncertain. Here, we used a Drosophila AD model expressing a secreted form of human amyloid-β42 peptide and showed that it recapitulates key aspects of AD pathology, including neuronal death and impaired long-term memory. We found that neuronal apoptosis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(81 citation statements)
references
References 65 publications
4
73
0
Order By: Relevance
“…Remarkably, increasing cell competition through expression of another copy of Azot, or expression of the apoptotic gene Hid under the Azot promoter, results in an increase in both lifespan and health span, as shown by a decrease in wing aberrations and neurodegenerative vacuoles. A more recent study by the same group has demonstrated that the Azot and Flower genes play a role in removing cells producing the amyloid-β42 peptide, a protein strongly implicated in Alzheimer's disease pathophysiology, and that this removal improves brain function (Coelho et al, 2018). Although similar findings have yet to be confirmed in mammalian systems, this study provides support for a role for cell competition in the clearance of damaged cells (Fig.…”
Section: Beneficial Roles In Adult Tissues Elimination Of Damaged Cellssupporting
confidence: 71%
See 1 more Smart Citation
“…Remarkably, increasing cell competition through expression of another copy of Azot, or expression of the apoptotic gene Hid under the Azot promoter, results in an increase in both lifespan and health span, as shown by a decrease in wing aberrations and neurodegenerative vacuoles. A more recent study by the same group has demonstrated that the Azot and Flower genes play a role in removing cells producing the amyloid-β42 peptide, a protein strongly implicated in Alzheimer's disease pathophysiology, and that this removal improves brain function (Coelho et al, 2018). Although similar findings have yet to be confirmed in mammalian systems, this study provides support for a role for cell competition in the clearance of damaged cells (Fig.…”
Section: Beneficial Roles In Adult Tissues Elimination Of Damaged Cellssupporting
confidence: 71%
“…Conversely, could cell competition mechanisms deteriorate with age, leading to a rise in age-related pathology? Although there is promising evidence to suggest that cell competition affects ageing in Drosophila (Coelho et al, 2018;Merino et al, 2015), opening up the investigation to mammalian systems will be crucial in establishing if altered cell competition dynamics can indeed be added to the hallmarks of ageing (López-Otín et al, 2013), and whether either boosting or blocking cell competition could therefore be a viable prevention strategy for age-associated disease.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Recent evidence challenges the notion that neuronal loss is universally detrimental in AD, since removal of damaged neurons may improve neuronal circuit function and functional outcomes (50). This raises the possibility that complementmediated neuroinflammation may initially be a compensatory mechanism in the face of AD pathology by removing misfolded proteins, cellular debris, and inactive synapses, and enhancing plasticity, neural repair, and neuroprotection (51).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we recently reported an unexpected protective role of cell competition against neurodegeneration, which involves the beneficial death of less fit neurons in amyloid-β-transgenic flies through fitness comparison (Coelho et al, 2018). Amyloid-β (Aβ) is a small peptide formed by the sequential cleavage of the transmembrane amyloid precursor protein (APP) by γand β-secretases and represents the main component of the extracellular amyloid plaques found in the brain of Alzheimer's disease (AD) patients (De Strooper et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of Aβ oligomers and plaques and subsequent hyper-phosphorylation and aggregation of the microtubule cytoskeleton-stabilizing Tau protein into neurofibrillary tangles are assumed to be the main pathological triggers of AD, but the sequence of events leading to neuronal death and cognitive failure is not understood (Braak and Braak, 1991;Karran and De Strooper, 2016). In Drosophila, neurons transit through a period of low fitness status when challenged by the ectopic expression of the human Aβ peptide and selective elimination of unfit neurons using cell competition machinery has a positive effect for the organism, halting the progression of motor and cognitive symptoms (Coelho et al, 2018).…”
Section: Introductionmentioning
confidence: 99%